Antibodies to Escherichia coli O157 in patients with haemorrhagic colitis and haemolytic uraemic syndrome. Issue 9 (September 1989) - Chart, H; Scotland, S M; Smith, H R; Rowe, B
Abstract : Twenty four sera from patients with haemolytic uraemic syndrome or haemorrhagic colitis and healthy controls were examined for antibodies to the lipopolysaccharide (LPS) of Escherichia coli O157. Faecal specimens from these patients were also examined for Vero cytotoxin producing E coli (VTEC) by DNA probes, and for faecal Vero cytotoxin. Eight patients with faecal E coli O157:H7 gave a strong antibody response to O157 LPS, shown by immunoblotting and an enzyme linked immunosorbent assay. Six symptomatic patients without evidence of faecal VTEC also gave a strong antibody response to O157 LPS. Sera from the remaining five patients and five healthy controls did not contain antibodies to E coli O157. The results suggest that the testing of sera from patients with haemorrhagic colitis or haemolytic uraemic syndrome by ELISA or immunoblot would prove valuable in addition to the established procedures for detecting VTEC, using DNA probes and testing for faecal Vero cytotoxin.